Neuroprotective potential of antioxidant potent fractions from Convolvulus pluricaulis Chois. in 3-nitropropionic acid challenged rats. (7th February 2016) - Kaur, Mandeep; Prakash, Atish; Kalia, Ajudhia Nath
Abstract : Objective : To isolate the neuroprotective component from Convolvulus pluricaulis Chois. ( Convolvulaceae ) which can be used as a lead molecule in the treatment of Huntington's disease (HD). Methods : The methanolic extract of whole plant was fractionated into four fractions; chloroform, ethyl acetate, n -butanol, and aqueous fraction. The chloroform and ethyl acetate fractions were pooled on the basis of antioxidant activity and TLC profile and charged into silica gel column. Four subfractions were collected from column (FrA, FrB, FrC, and FrD) and further assessed for antioxidant potential by 2, 2-diphenyl-1-picrylhydrazyl in vitro assay. 3-Nitropropionic acid (3-NP) was administered to Wister rats for induction of HD. Different fractions were administered for 14 days. Different behavioral alterations were assessed in between study period. Animals were euthanized immediately following the last behavioral session, and biochemical parameters were measured. Result and discussion : Systemic administration of 3-NP showed marked motor deficits and oxidative damage in rats. Only FrB showed significant antioxidant activity and on further purification gave pure compound (scopoletin). Our study showed that FrB (20 mg/kg) pre-treatment significantly attenuated the loss in body weight, improved the locomotor activity, grip strength, and gait abnormalities. It also has attenuated the increased malondialdehyde and nitrite levels, and restored superoxide dismutase and reduced GSH enzyme activity in the striatum and cortex in 3-NP-treated groups. These results suggest that C. pluricaulis Chois. exhibits a neuroprotective effect by accelerating brain antioxidant defense mechanisms in 3-NP-treated rats.